Requirement analysis: users’ involvement in IS model development - Thong, C. L.; Jusoh, Yusmadi Yah; Abdullah, Rusli; Haizan Nor, Rozi Nor (Science and Engineering Research Support Society, 2019)
The active involvement of the users (also known as curriculum designers in this study) in designing curriculum in Institution of Higher Learning (IHL)is important. Earlier study conducted shown that curriculum designers face challenges such as mapping course learning outcomes to programme learning outcomes and calculating student learning time manually requires much effort.The curriculum design process also faced problems such as error-prone and consume a lot of time. This paper presents the results of gathering and analyzing user requirements during the development of a proposed model, named as information System Curriculum Design (ISCD) model. The requirement analysis consists of literature review on the existing systems and a survey on ducted among 90 curriculum designers from 20 IHL. The respondents who have at least one year experience in curriculum design have verified the components and subcomponent of ISCD model by indicating their perception o the importance of these components. The overall results show that all components and subcomponents are perceived important by curriculum designers in IHL and the relationships are positively related to each other.